Optimizing Strategies for Sustainable Mango Agribusiness: A Case Study on Agricultural Extension Centres in Sukorejo District - Nuarie, L. Restu Bayu; Sugiyanto, Sugiyanto; Cahyono, Edi Dwi (Kadiri University - Faculty of Agriculture, 2024)
The important role of the Agricultural Extension Centre (AEC) at the sub-district level is indispensable in overcoming challenges and capitalizing on opportunities in the agribusiness sector. This study aims to illustrate important strategies that can strengthen the contribution of AEC in supporting agribusiness sustainability, with a particular focus on the mango commodity. This study used qualitative methodology and concentrated on a case study conducted at AEC Sukorejo Sub-district, Pasuruan Regency, which implements the Agricultural Development Command Strategy Program (Kostratani). Data were carefully collected through interviews with five agricultural extension workers, complemented by comprehensive field observations. Analysis was conducted through the Strength, Weakness, Opportunity, Threat (SWOT) method by carefully examining the internal dynamics of AEC. Research findings reveal AEC's internal strengths, including in-depth local knowledge, strong networks with farmers, and active participation of farmers in government programs. However, the identified weaknesses, such as limited human resources, budget constraints, and internal coordination issues, require concerted efforts to resolve in order to fully leverage the potential of modern technological advances in the Kostratani program. Priority strategies recommended for implementing AEC include focused initiatives to organize intensive training sessions on mango agribusiness practices, integrating the latest information and communication technologies. In addition, developing sophisticated digital applications is proposed to facilitate the seamless exchange of information and encourage dynamic discussions among farmers, ultimately strengthening partnerships with the mango industry.